Homatula gelao (Cypriniformes, Nemacheilidae), a new nemacheiline species of loach from the upper Yangtze River basin in Guizhou Province, southwestern China - Gui-Bang Xiao; Qi-Wei Guo; Liang Cao; Jia Lin; Wei-Xi Deng; Qi-Qi Xiao; Lin Zhou; Hao-Ran Zhang; Ding-Zhi Fang (Zoosystematics and Evolution)
Homatula gelao, a new species, is here described from the Wu-Jiang of the Yangtze River basin in Guizhou province, southwestern China. This new species belongs to the elongate-bodied group of Homatula defined by having a complete lateral line, sparsely scales hidden in skin on the predorsal body, and a slender body with a uniform depth. It, along with H. variegata, is distinguished from all other species of this group in having a broadly rounded caudal fin and a small number of scales sparsely scattered over the predorsal body. Both differ in body coloration, striped pattern on the predorsal body, and caudal-peduncle length. The validity of the new species is corroborated by distinct genetic distance divergence with closely related congeneric species and its monophyly recovered in a mtDNA COI gene-based phylogenetic analysis. It is separated from other Homatula species by a minimum of 8.2% Kimura 2-parameter distance in the COI gene.